Micoteca da Universidade do Minho (MUM): implementation of a Quality Management System based on ISO 9001:2008 - Simões, Marta Filipa (2011)
Micoteca da Universidade do Minho (MUM, www.micoteca.deb.uminho.pt) is a filamentous fungi culture collection established in May 1996 by the Universidade do Minho Rectorate, hosted by the Biological Engineering Centre, which is a centre of excellence integrated in the Institute for Biotechnology and Bioengineering (IBB, www.ibb.pt). In order to keep its high standards MUM has implemented a Quality Management System (QMS) based on the normative reference NP EN ISO 9001:2008 and the OECD Best Practices, 2007.